Design and Development of a Stainless Steel Fermentation Tank for Palm Wine with Gravity Purification Construction - Robot, Jimmy Reagen; Tuturoong, Nancy Jeane; Rembet, Michael Edward; Mononutu, Edmond C. (International Journal of Contemporary Sciences (IJCS), 2024)
Tourism and culinary activities are increasingly integrated into wine tourism, a key segment of agricultural tourism. Palma wine, a traditional wine produced from the sap of palm trees (locally known as sagars), is a significant product for the Minahasa farming community in North Sulawesi. This study focuses on optimizing the fermentation process to enhance the quality of Palma wine by utilizing food-grade HDPE containers and a dual-role fermentation tank. The tank is designed to reduce dust content in the palm sap through an efficient mechanism while minimizing disruptions during the transfer of fermentation products. The research involves designing and testing fermentation tanks based on applied science and technology principles to improve purification processes and standardize effectiveness and efficiency measurements. Results demonstrate that the use of high-quality fermentation tanks enhances the purification process and ensures better-quality Palma wine, contributing to the development of local wine tourism and supporting sustainable agricultural practices.